2000
DOI: 10.1034/j.1398-9995.2000.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and rhinitis in relation to long‐term exposure to gaseous air pollutants

Abstract: The relationship between long-term exposure to air pollutants, especially with regard to photochemical air pollutants, and asthma prevalence in developed countries is controversial. The objective of this cross-sectional survey was to compare mean levels of the main gaseous air pollutants and prevalence rates of rhinitis, asthma, and asthmatic symptoms. It included 2,445 children from the 8th and 9th school grades who had been living for at least 3 years in an area where some communities undergo the heaviest ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 22 publications
0
34
1
2
Order By: Relevance
“…Table 4 showed the associations between the prevalence of childhood rhinitis and average site-specific background levels of air pollutants and age-related personal accumulative exposure by using multivariate logistic regression models. Children's diagnosed allergic rhinitis was not statistically significantly associated with average background concentrations of the three pollutants, but significantly related with age-related personal accumulative exposure of 10 , SO 2 and NO 2 were significantly positively associated with allergic rhinitis. An increase of 10 g/m 3 in age-related personal accumulative exposure to PM 10 , SO 2 and NO 2 may lead to an increase in the prevalence of children's rhinitis by 2.1% (95% CI, 0.3%-3.9%), 2.6% (95% CI, 0.5%-4.8%) and 3.7% (95% CI, 0.6%-6.9%), respectively.…”
Section: Air Pollution and Allergic Rhinitismentioning
confidence: 91%
See 3 more Smart Citations
“…Table 4 showed the associations between the prevalence of childhood rhinitis and average site-specific background levels of air pollutants and age-related personal accumulative exposure by using multivariate logistic regression models. Children's diagnosed allergic rhinitis was not statistically significantly associated with average background concentrations of the three pollutants, but significantly related with age-related personal accumulative exposure of 10 , SO 2 and NO 2 were significantly positively associated with allergic rhinitis. An increase of 10 g/m 3 in age-related personal accumulative exposure to PM 10 , SO 2 and NO 2 may lead to an increase in the prevalence of children's rhinitis by 2.1% (95% CI, 0.3%-3.9%), 2.6% (95% CI, 0.5%-4.8%) and 3.7% (95% CI, 0.6%-6.9%), respectively.…”
Section: Air Pollution and Allergic Rhinitismentioning
confidence: 91%
“…Routinely monitored data for PM 10 (particles with an aerodynamic diameter of 10 m or less), sulphur dioxide (SO 2 ) and nitrogen dioxide (NO 2 ) are available from Changsha Environmental Protection Agency. Daily concentrations of each pollutant were measured continuously and reported by the website of Changsha Common Meteorologic Information Service (http://www.csqx.com/).…”
Section: Exposure Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The U.S. EPA review of animal tests and epidemiologic studies of ozone (61) concluded that chronic effects may be associated with long-term exposure to ozone. Increases in the prevalence of asthma (62), as well as exacerbation of asthma (47,56,63), have been found to be associated with long-term exposure to ozone. There is also some evidence of effects of ozone at levels below current air quality standards (20,64).…”
Section: Ozonementioning
confidence: 99%